THE DISTRIBUTION AND ASYMMETRY OF MAMMALIAN CELL SURFACE SACCHARIDES UTILIZING FERRITIN-CONJUGATED PLANT AGGLUTININS AS SPECIFIC SACCHARIDE STAINS - Nicolson, Garth L. (The Rockefeller University Press, 1974)
The preparation, properties, and some applications of ferritin conjugates of two plant agglutinins, concanavalin A and Ricinus communis agglutinin, are reported. These conjugates serve as specific electron-dense stains for cell- and membrane-bound saccharide residues of the α-D-mannopyranosyl and β-D-galactopyranosyl configurations, respectively, and as examples of a wide range of ferritin-plant agglutinin conjugates useful as high resolution saccharide stains. By using a technique for preparing flattened membrane specimens, it was found with a variety of mammalian cell plasma membranes (lymphocyte, lymphoma, and myeloma and normal, spontaneously and virally transformed fibroblasts) that the ferritin conjugates were localized exclusively to the exterior face of the membrane, with essentially none found on the cytoplasmic face. On the exterior face the topographical distribution of ferritin conjugates appeared to be random. The asymmetrical distribution of saccharide residues to the outer membrane face can be explained by an "assembly line" process whereby new plasma membrane is made from intracellular precursor membranes. It also suggests that the saccharide-containing components of the plasma membrane do not rotate at any appreciable rate from one membrane surface to the other.